NGO Presence and Activity in Afghanistan, 2000–2014: A Provincial-Level Dataset. Issue 1 (13th June 2017) - Mitchell, David F.
This article introduces a new provincial-level dataset on non-governmental organizations (NGOs) in Afghanistan. The data—which are freely available for download—provide information on the locations and sectors of activity of 891 international and local (Afghan) NGOs that operated in the country between 2000 and 2014. A summary and visualization of the data is presented in the article following a brief historical overview of NGOs in Afghanistan. Links to download the full dataset are provided in the conclusion.